Editorial: Hayek, Keynes and the Crisis: Analyses and Remedies. An Introduction - Ferlito, Carmelo (Journal of Reviews on Global Economics, 2015)
I am glad to present to the readers of the Journal of Reviews on Global Economics this special issue titled "Hayek, Keynes and the crisis. Analyses and Remedies", named after a scientific conference which was held between 22 and 24 January 2015 at the Amphithéâtre Vedel, Université Paris-Sud, Faculté Jean Monnet, Sceaux, in France. The conference was organized by the Research Centres of the Université Paris-Sud “Collège d’Etudes Interdisciplinaires" and “Réseaux Innovation Territoires et Mondialisationâ" and sponsored by the International Journal of Political Economy, the Review of Keynesian Economics, the book series"New Directions in Post-Keynesian Economics" (published by Edward Elgar), the Association pour le Développement des Etudes Keynésiennes and the Association Française d’Economie Politique. Important scholars from all around the world answered the call from Bernard Vallageas and François Facchini in order to discuss the heritage, for present day economics, of the Hayek/Keynes controversy, developed during the 1930s. The controversies between Hayek and Keynes began in 1929 when Hayek, presented his lectures on business cycles at the London School of Economics, invited by Lionel Robbins. The opposition appeared in their respective books Prices and Production, Monetary Theory and the Trade Cycle, A Treatise on Money and their comments on these books published in journals. The object of the conference was to analyze the controversies between Hayek and Hayekians on one side and Keynes and Keynesians on the other side. This special issue hosts some of the contributions presented during that conference (Levy Orlik, Facchini, Sanz Bas and Morillo, Ferlito). However, together with the JRGE editors we decided to open the debate to a wider spectrum of scholars and the papers here published are the result of a call for papers on the topic. We are therefore glad to present here original contributions by Heinz D. Kurz, AndrÃ© Getzmann, Sebastian Lang, Klaus Spremann, Max Gillman and Giovanni Bella. We open the special issue with the paper by Heinz D. Kurz, who brings new light on the debate on crises and cycles between Hayek, Keynes and Sraffa; in particular, prof. Kurz demonstrates how Sraffa, while strongly criticizing the Hayek’s perspective, at the same time did not support Keynes’ view. The theme will be reprised in my paper, published as the last one, in which the Sraffa/Hayek debate is analyzed with Lachmann’s eyes; the German economist, in looking for microfoundations for the capital analysis, accused Sraffa and the Cambridge School to develop a new neo-Ricardian approach, grounded on macroformalism and aggregation. Noemi Levy Orlik, while discussing Hayek and the Austrian monetary school innovative ideas in terms of money in capitalist economies, embraces a new-Keyensian view according to which the main way to overcome economic activity fluctuations is to implement expansive fiscal policies, opposing wages cuts, and promoting financial market regulation. A conciliatory approach is instead proposed by François Facchini, who explains how the regulated capitalism is the cause of market instability and financial fragility: moral hazard encourages commercial banks to take risks and therefore post-2008 crisis policies went in the wrong direction. David Sanz Bas and Juan Morillo come back to the main issue, the Hayek/Keynes debate, and demonstrate how the general idea according to which, after the debate on the Treatise on Money Hayek renounced to criticize The General Theory, is wrong. We need instead to accurately read post-1936 Hayek’s works to find how a wide criticism can be found. André Getzmann, Sebastian Lang and Klaus Spremann try to combine Hayek’s and Keynes’ approaches looking at companies’ decisions to finance investments and at their agility to adjust their capital structure. They then study the relationship between capital structure to finance corporate production and shifts in aggregate demand. Their results provide evidence for Keynes’ General Theory from a firm level perspective: firms respond very fast to aggregate demand by adjusting capital and production structure correspondingly. Giovanni Bella contributes to the new Keynesian literature by showing that stable endogenous cycles can emerge as equilibrium solutions of the traditional IS-LM model. The application of the original Bogdanov-Takens theorem allows him to determine the regions of the parametric space where the model exhibits a global indeterminate solution, and a low-growth trapping region, characterized by a continuum of equilibrium trajectories in the proximity of a homoclinic bifurcation. Finally, Max Gillman retrospectively look at how Hayek’s and Fisher’s idea on the Great Depression arose as opposed to Keynes’ interventionism. Through an interesting quantitative analysis, Gillman demonstrate that the present Great Recession calls for free market oriented policies and not for further pro-active policies.